Akomodasi Virus N Ach Terhadap Etos Kerja Islami Sebagai Motivasi Kerja - Kholilur Rahman (Fakultas Ekonomi dan Bisnis Islam (FEBI), Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2018)
Human beings as psycho-physical who can produces work ethics that appears from inside of themselves soul, necessarily, the realm of analytical studies leads to motivational psychology. N Ach is one of the proper phenomena which is assumed to be something that can play an important role for the formation of superior human beings regarding to work. However, not all psychology scientists agree that work motivation comes from revelation or religion, therefore this study will clarify psychological studies which are considered to have proportional accommodative attitudes. Religion Psychology, Transpersonal Psychology and Humanistic Psychology are thought schools those have fair and objective attitudes and views on the Islamic teachings and Islamic dogma as a source of work motivation. People who have high N Ach and also the person who actualized it is a factors or elements that can emerge a high work ethic, then it shows that there is a potential high work ethic from muslim’s faith that was built on the basics of Al-Qur 'an and As-Sunnah. Faith without worship acts/work which was included abaout physical and psychological work, so also if the work ethic is not based on the concept of worship acts and fitht, it cannot be categorized as Islamic work. Then it was called the Islamic work ethic.